Classification of the types of load bearing systems and vests for military personnel - Tokar, G.; Ostapenko, N.; Tretyakova, L.; Lutsker, T. (Theory and practice of design, 2017)
In the article the existing vest load bearing systems are analyzed, systemized and discussed in historical perspective. On the basis of theoretical studies, the main varieties of unloading systems are determined in the plane of historical development. The structural and technological solutions are analyzed and systematized, the features of designing and manufacturing of the product as a whole and its elements are singled out. The main types of vest load bearing systems are singled out. The data about the design and technological solutions of these items is analyzed and generalized. The classification of the elements of vest load bearing systems in relation to their different features is developed (by type of adjustment in size and height, fasteners, connection of shoulder straps with a belt, fastening of the results, forms, evacuation loops and the possibility of using a soft ballistic package).